1995
DOI: 10.1046/j.1468-2982.1995.015002123.x
|View full text |Cite
|
Sign up to set email alerts
|

Contingent Negative Variation During Migraine Attack and Interval: Evidence for Normalization of Slow Cortical Potentials During the Attack

Abstract: The contingent negative variation (CNV) amplitudes of 16 subjects with migraine without aura were studied during pain-free intervals and during attacks and the results were compared with those of 22 healthy subjects. In 32 trials the CNV amplitudes were calculated for (a) "total interval", (b) "early CNV component", (c) "late CNV component", and (d) habituation. There was a significantly higher total CNV amplitude in migraine subjects during pain-free intervals compared to that of the healthy subjects and migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
140
4
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(166 citation statements)
references
References 15 publications
19
140
4
3
Order By: Relevance
“…[34][35][36][37][38][39][40][41][42][43] The first evidence for altered interictal habituation in patients with migraine came from studies of contingent negative variation (CNV), a slow event related corti cal response representing higher mental functions. [44][45][46][47] Subsequently, deficient habituation was demonstrated for another event related potential, P300, which is eli cited in the process of decision making after visual 48 or auditory 49,50 stimulation. Deficient habitu ation was also subsequently described for several other modality specific evoked potentials: pattern reversal visual evoked potentials (VEPs), [33][34][35][36][37][38][39][40][41][42] visual evoked magneto encephalographic (MEG) responses, 43 auditory evoked potentials (AEPs), 51,52 and somatosensory evoked poten tials (SSEPs).…”
Section: Impaired Habituationmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41][42][43] The first evidence for altered interictal habituation in patients with migraine came from studies of contingent negative variation (CNV), a slow event related corti cal response representing higher mental functions. [44][45][46][47] Subsequently, deficient habituation was demonstrated for another event related potential, P300, which is eli cited in the process of decision making after visual 48 or auditory 49,50 stimulation. Deficient habitu ation was also subsequently described for several other modality specific evoked potentials: pattern reversal visual evoked potentials (VEPs), [33][34][35][36][37][38][39][40][41][42] visual evoked magneto encephalographic (MEG) responses, 43 auditory evoked potentials (AEPs), 51,52 and somatosensory evoked poten tials (SSEPs).…”
Section: Impaired Habituationmentioning
confidence: 99%
“…Evers et al [57] have shown in migraineurs that habituation, assessed by a latency increase of the event-related visual P300 response, varies inversely with platelet serotonin content; in particular, it arguments, i.e., normalizes, during the attack in parallel with a decrease in platelet serotonin. Normalization of amplitude habituation during the attack was also found for VEPs [58] and CNV [59]. In a recent study, Siniatchkin et al [43] demonstrate that migraine patients are characterized by two kinds of habituation deficits compared with healthy subjects: (a) the sensory gating deficit or reduced STH of the P50 wave, independent of attentional demands to the stimulation, and (b) the LTH of the P300 wave under circumstances of increased cortical processing and enhanced mobilization of attentional resources.…”
mentioning
confidence: 55%
“…Various studies have demonstrated a more negative bCNV in patients with migraine during foreperiods that are shorter than 2 s [74]. Studies employing longer foreperiods predominantly report a higher early wave amplitude in migraine without aura [75][76][77], but higher late wave amplitudes have also been reported [75]. The higher CNV amplitudes are believed to emerge as a result of the slow habituations over trials [74,76,78].…”
mentioning
confidence: 99%
“…In addition, VEP and IDAP as well as CNV were found to undergo marked changes in temporal relation to the attack. Amplitudes tended to normalize during the attack [62], but they increased 2 days before the attack and returned to interictal levels during the days following the attack [69,73,74]. In most previous studies of evoked-or event-related potentials, the delay between the recordings and the next attack was not determined, which may in part account for the variability of findings.…”
Section: Psychophysical Studies Of the Visual Pathwaysmentioning
confidence: 99%